2015
DOI: 10.3109/1061186x.2015.1073294
|View full text |Cite
|
Sign up to set email alerts
|

Efficient “green” encapsulation of a highly hydrophilic anticancer drug in metal–organic framework nanoparticles

Abstract: Metal-organic frameworks (MOFs) are coordination polymers of interest for biomedical applications. Of particular importance, nanoparticles made of iron(III) trimesate (MIL-100, MIL standing for Material Institut Lavoisier) (nanoMOFs) can be conveniently synthesised under mild and green conditions. They were shown to be biodegradable, biocompatible and efficient to encapsulate a variety of active molecules. We have addressed here the challenges to encapsulate a highly hydrophilic anticancer prodrug, phosphated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 50 publications
9
62
0
Order By: Relevance
“…This means that macrophages differ significantly in their ability to recognize uncoated and PEGylated MIL‐100 NPs, i.e., surface PEG chains on MIL‐100(Fe) endorse a significant furtiveness effect by preventing the rapid recognition from macrophages. These results are in agreement with some previous observations, where MIL‐100(Fe) encapsulation was already demonstrated effective to perform intracellular transport of this drug …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This means that macrophages differ significantly in their ability to recognize uncoated and PEGylated MIL‐100 NPs, i.e., surface PEG chains on MIL‐100(Fe) endorse a significant furtiveness effect by preventing the rapid recognition from macrophages. These results are in agreement with some previous observations, where MIL‐100(Fe) encapsulation was already demonstrated effective to perform intracellular transport of this drug …”
Section: Resultssupporting
confidence: 93%
“…A plausible solution to overcome GMP degradation and to reach the tumor cells results from the encapsulation/protection of GMP in porous nanocarriers such as nanoMOFs. In this line, MIL‐100(Fe) GMP encapsulation was already demonstrated effective to perform intracellular transport of this drug . In addition, previous studies demonstrated that 5 kDa PEG has the maximal capacity to reduce protein adsorption and thus, guarantee macrophage avoidance .…”
Section: Resultsmentioning
confidence: 97%
“…The increase of α (from 0.22 for the control to 0.36) shows that direct lethal damages are increased. This corresponds to the well‐known effect of the drug, which agrees with former studies . Thus, upon irradiation, the agent induces radiosensitization of the cells, namely an amplification of radiation effect due to perturbation of a metabolic pathway.…”
Section: Resultssupporting
confidence: 89%
“…[5,9] In this challenging context, some of us have shown that Gem-MP could be protected against degradation with increased cellular uptake by encapsulation in nanoparticles (NPs). [10] Nanotechnology has proven the effectiveness to target tumors, strategy of particular interest for drug delivery by achieving drug transcytosis, drug targeting and theranostics. [11,12] In addition to the benefits of NPs for drug delivery, the potential value of metal based NPs as radioenhancers has been discovered in 2000.…”
Section: Introductionmentioning
confidence: 99%
“…As observed for single drug encapsulation, coincorporation of AMOX and CL neither altered the nanoMOF crystalline structure (identical X‐ray diffraction patterns, Figure S2, Supporting Information) nor their morphology (Figure b). After coincorporation of both drugs at their maximal loadings (13 and 22 wt% for AMOX and CL, respectively) there was less than 10% variation of the mean NP diameters (273 ± 23 and 298 ± 9 nm, before and after drug loading, respectively).…”
Section: Resultsmentioning
confidence: 61%